New insights into the column CH2O/NO2 ratio as an indicator of near‐surface ozone sensitivity. Issue 16 (17th August 2017) - Schroeder, Jason R.; Crawford, James H.; Fried, Alan; Walega, James; Weinheimer, Andrew; Wisthaler, Armin; Müller, Markus; Mikoviny, Tomas; Chen, Gao; Shook, Michael; Blake, Donald R.; Tonnesen, Gail S.
Abstract: Satellite‐based measurements of the column CH2 O/NO2 ratio have previously been used to estimate near‐surface ozone (O3 ) sensitivity (i.e., NO x or VOC limited), and the forthcoming launch of air quality‐focused geostationary satellites provides a catalyst for reevaluating the ability of satellite‐measured CH2 O/NO2 to be used in this manner. In this study, we use a 0‐D photochemical box model to evaluate O3 sensitivity and find that the relative rate of radical termination from radical‐radical interactions to radical‐NO x interactions (referred to as LRO x /LNO x ) provides a good indicator of maximum O3 production along NO x ridgelines. Using airborne measurements from NASA's Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relative to Air Quality (DISCOVER‐AQ) deployments in Colorado, Maryland, and Houston, we show that in situ measurements of CH2 O/NO2 can be used to indicate O3 sensitivity, but there is an important "transition/ambiguous" range whereby CH2 O/NO2 fails to categorize O3 sensitivity, and the range and span of this transition/ambiguous range varies regionally. Then, we apply these findings to aircraft‐derived column density measurements from DISCOVER‐AQ and find that inhomogeneities in vertical mixing in the lower troposphere further degrades the ability of column CH2 O/NO2 to indicate near‐surface O3 sensitivity (i.e., the transition/ambiguous range is much larger than indicated by in situ data alone), and we hypothesize that the global transition/ambiguous range is sufficiently large to make the column CH2 O/NO2 ratio unuseful for classifying near‐surface O3 sensitivity. Lastly, we present a case study from DISCOVER‐AQ‐Houston that suggests that O3 sensitivity on exceedance days may be substantially different than on nonexceedance days (which may be observable from space) and explore the diurnal evolution of O3 sensitivity, O3 production, and the column CH2 O/NO2 ratio. The results of these studies suggest that although satellite measurements of CH2 O/NO2 alone may not be sufficient for accurately classifying near‐surface O3 sensitivity, new techniques offered by geostationary platforms may nonetheless provide methods for using space‐based measurements to develop O3 mitigation strategies. Key Points: In situ measurements of the CH2 O/NO2 ratio are a good indicator of ozone sensitivity but are spatially limited in their coverage Column measurements of CH2 O/NO2 are a poor indicator of near‐surface ozone sensitivity due to uneven vertical mixing in the lower troposphere Long‐ and short‐term observations of changes in column CH2 O/NO2 ratios may still provide useful information about the relative importance of O3 precursors